Distance Education Research in South Africa: A Longitudinal Study into the Research Levels of ODL Journal Articles - Roberts, Jennifer; van der Walt, Hugo Denton (Mousaion: South African Journal of Information Studies, 2023)
The measure of an academic field lies in the richness and depth of its published research, especially within the ever-developing field of distance education, which is relatively new. The University of South Africa is one of the oldest open distance learning (ODL) higher education institutes globally, which has given rise to its status internationally as a leader of distance education. It is prudent to analyse and reflect on the research outputs published by South African academics, particularly regarding the levels of research that are conducted. This article follows the research published by Roberts, which analysed South African distance learning research levels and sublevels from articles published between 2011 and 2015. This longitudinal study applied a thematic content analysis of the titles and abstracts of all ODL-related papers published by South African authors. The findings compare ODL trends for the five-year periods from 2010 to 2014 and 2015 to 2019. The data were obtained from the Scopus and SABINET databases, using the same search criteria employed by Roberts. The levels of research publications were analysed according to the open distance learning research framework of Zawacki-Richter presented through descriptive statistics. The results indicate that although the number of published open distance learning research articles has more than doubled, the research levels have not shown any significant change from the previous five years. The South African ODL publications should give attention to meso- and macro-level research to enhance the ODL development within Southern Africa and create local trends fit for purpose.